Germline variants of CYBA and TRPM4 predispose to familial colorectal cancer - Zhu, Lizhen; Miao, Beiping; Dymerska, Dagmara; Kuswik, Magdalena; Bueno-Martínez, Elena; Sanoguera-Miralles, Lara; Velasco, Eladio A.; Paramasivam, Nagarajan; Schlesner, Matthias; Kumar, Abhishek; Yuan, Ying; Lubinski, Jan; et al. (Cancers, 2022)
Familial colorectal cancer (CRC) is only partially explained by known germline predisposing genes. We performed whole-genome sequencing in 15 Polish families of many affected individuals, without mutations in known CRC predisposing genes. We focused on loss-of-function variants and functionally characterized them. We identified a frameshift variant in the CYBA gene (c.246delC) in one family and a splice site variant in the TRPM4 gene (c.25-1 G > T) in another family. While both variants were absent or extremely rare in gene variant databases, we identified four additional Polish familial CRC cases and two healthy elderly individuals with the CYBA variant (odds ratio 2.46, 95% confidence interval 0.48-12.69). Both variants led to a premature stop codon and to a truncated protein. Functional characterization of the variants showed that knockdown of CYBA or TRPM4 depressed generation of reactive oxygen species (ROS) in LS174T and HT-29 cell lines. Knockdown of TRPM4 resulted in decreased MUC2 protein production. CYBA encodes a component in the NADPH oxidase system which generates ROS and controls, e.g., bacterial colonization in the gut. Germline CYBA variants are associated with early onset inflammatory bowel disease, supported with experimental evidence on loss of intestinal mucus barrier function due to ROS deficiency. TRPM4 encodes a calcium-activated ion channel, which, in a human colonic cancer cell line, controls calcium-mediated secretion of MUC2, a major component of intestinal mucus barrier. We suggest that the gene defects in CYBA and TRPM4 mechanistically involve intestinal barrier integrity through ROS and mucus biology, which converges in chronic bowel inflammation.